Liver transplantation in a patient with massive polycystic liver disease: A case report and literature review. (September 2022) - Deng, Qingsong; Liu, Fenghao; He, Minglian; Ou, Yanjiao; Zhang, Leida
Abstract: Introduction and importance: Liver transplantation (LT) is rarely performed and challenging but is the only curative treatment option for severe polycystic liver disease (PLD). LT can cause hemorrhage and is not standardized. We performed a routine operation for smooth, giant liver cysts, with minimal intraoperative bleeding. Case presentation: We report a case of a 38-year-old female who was hospitalized for emaciation with abdominal distension for 5 years that became worse for 1 year. She was diagnosed with massive PLD complicated by liver cirrhosis, splanchnic varices and ascites that led to reduced activity, diminished ability to live independently and reduced quality of life; she successfully underwent LT. Clinical discussion: The patient had a large volume of hepatic cysts and little normal liver parenchyma, resulting in obvious clinical symptoms untreatable with routine surgery. The only curative surgical option for patients with severe symptoms is LT. The patient recovered smoothly after LT. We conclude that the only radical method for treating large polycystic liver lesions is LT in a conventional operation. Intraoperative bleeding was minimal. The anhepatic phase and revascularization time did not differ from those of conventional LT. The patient recovered well postoperatively. Conclusion: A literature review suggests that the only radical treatment for giant polycystic liver is LT. At present, most of the literature is case reports or summary analyses of a small sample of cases. A long-term (more than 20 years) survival analysis suggests that LT has a low incidence of surgical complications and a good long-term curative effect. Highlights: Liver transplantation for severe polycystic liver disease is rare. The only radical treatment for giant polycystic liver is liver transplantation. The surgery caused minimal intraoperative bleeding.